Effect of Pulsed Low-Level Lasers on Adult versus Neonatal Human Retinal Pigment Epithelial Cells: An In-vitro Study - Moshtaghion, Seyed Mohamadmehdi; Abolhosseini, Mohammad; Tabeie, Faraj; Balagholi, Sahar; Suri, Fatemeh; Karami, Samira; Naraghi, Houra; Rezaei Kanavi, Mozhgan; Asadi, Somayeh (Journal of Ophthalmic and Vision Research, 2024)
Purpose: To investigate the short-term effects of low-level lasers (LLLs; also known as lowpower laser therapy) on the structure, genetic, and phenotype of cultured human retinal pigment epithelial (hRPE) cells from both adult and neonatal sources. Methods: Cultivated adult and neonatal hRPE cells were irradiated with two types of LLL (630 nm and 780 nm), 1 min daily for five consecutive days. Results: An increase in doubling time was observed in 630 nm-irradiated adult hRPE cells (P = 0.032). The gene expression profile revealed increased expression of retinoid isomerohydrolase RPE65 (RPE65) (P < 0.01 for 630 nm laser, P < 0.001 for 780 nm laser) and nestin (NES) (P < 0.01 for 630 nm laser) in neonatal hRPE cells, upregulation of RPE65 (P < 0.001 for 780 nm laser) and paired box 6 (PAX6) (P < 0.001 for 780 nm laser) genes in adult hRPE cells, and reduced expression of actin alpha 2 (ACTA2) in 780 nm-irradiated adult hRPE cells (P < 0.001). Except the significant increase of α-SMA in 780 nm-irradiated neonatal hRPE cells, no significant change was noted in the expressions of other investigated proteins. Conclusion: Short-term irradiation of neonatal and adult hRPE cells with LLLs may induce multipotency at the transcriptional level. Irradiation of neonatal hRPE cells with LLLs can be associated with increased risk of myofibroblastic transformation; however, adult hRPE cells irradiated with the 780 nm laser have minimal risk of myofibroblastic differentiation. It seems that the 780 nm laser may be a promising option for future photobiomodulation in retinal degenerations in adults.